Ketahanan Pangan Melalui Tanaman Hidroponik di Desa Melintang: Food Security Through Hydroponic Plants in Melintang Village - Nurfadillah, Mursidah; Fauziah, Fenty; Kustiawan, Paula Mariana; Anitra, Vera; Al Farauqi, Mohamad Dziqie Aulia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Desa Melintang is one of the villages in East Kalimantan Province located in the Kota Bangun area, Muara Wis District, Kutai Kartanegara Regency, East Kalimantan Province. The area is a water or lake region, so Desa Melintang is situated above the water. With such regional conditions, Melintang village does not have land that can be used for gardening or farming due to the absence of land or soil. This affects the vegetable needs, which cannot be produced by the people of Melintang Village themselves, so they have to be brought in from outside the region to. The long distance traveled to obtain vegetables makes it necessary for the community to spend more time dan money if they want to get vegetables. Based on the aforementioned issues, the PKM team conducted community service activities by providing hydroponic plant training to the PKK mothers' group in Melintang Village, while also donating hydroponic equipment dan supplies to the community. The results of the activity are expected to be beneficial in increasing the community's knowledge about hydroponic plants. In addition, by producing their own vegetables, the quality or freshness of the vegetables can be better guaranteed, dan the community can also save on expenses, which is expected to impact food fulfillment dan improve the welfare of the community.